A new compression technique in MANET: compressed-LZW algorithm - Hadeel Noori Saad; Fairouz mushtaq Jafar; Hanan Abbas Salman (Institute of Advanced Engineering and Science, 2019)
Now a days mobile ad hoc networks MANETs play a vital role in tremendous communication applications. This networks require infrastructure less module in non- centralized application’s area. Low battery power is of great concern to sustain for a long time, thus researchers try to assist in this critical maintenance point. This work proposed an enhanced version of well-known compression technique LZW to reduce data communication and maintain battery life. Compressed-LZW is a technique to code data stream into further compact form by merging successive redundant compressed code, and achieved by padding the code stream with the displacement of the next similar code. Compressed-LZW outperform its successor in saving consumed energy as expressed in the implementation and results by generating less output codes.